Sosialisasi Budidaya Lebah Trigona sp. di Desa Barudua, Kecamatan Malangbong, Kabupaten Garut - Alifah Fidela; Agesti Hasna Ekawati; Jakaria (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Barudua Village, Malangbong Subdistrict, Garut Regency is an agrotourism village with many strawberry plants. The majority of Barudua villagers are strawberry farmers. Barudua villagers consider the production of strawberry plants to meet the needs of the Barudua villagers. It's just that strawberry production has begun to decrease. So that community service activities are carried out aimed at providing knowledge to strawberry farmers about the use of bee Trigona sp. which can help potential pollination of strawberry and bee Trigona sp. can also produce honey that has a high selling value. The main target of the socialization of Trigona sp. this is a strawberry farmer in Barudua Village. Malangbong District, Garut Regency. The method used in this activity is the delivery of material and evaluation of activities. Based on the results of activities that have been carried out that all participants, especially the strawberry farmers, were very enthusiastic listening to the socialization material and played an active role during the question and answer process about the importance of Trigona sp. which is very influential in the productivity of strawberry plants. Besides being able to help the productivity of strawberry plants, Trigona sp. can also produce honey that has a high selling value. The effort to produce honey is expected to increase the income of strawberry farmers, especially the people of Barudua Village, Malangbong District, Garut Regency. After the socialization of Trigona sp. this time, the strawberry farmers well received the socialization of beekeeping, and in its implementation the strawberry farmers were very enthusiastic listening to the socialization material and played an active role during the question and answer process about the importance of beekeeping Trigona sp. which is very influential in the productivity of strawberry plants. Keywords: pollination, strawberry, Trigona sp bee